Analysis and Valuation of Netflix, Inc. - Nogueira Baptista, Maria Miguel (2024)
The aim of this master thesis is to analyze and understand Netflix, Inc. business, evaluate its position within the industry and determining its intrinsic value. The valuation date was set to April 16, 2024. The first chapter provides an overview of Netflix Inc., including its history, business model and stock performance. In the subsequent chapter, a detailed analysis of the media and entertainment industry is presented, examining key trends, competitors and market dynamics, for a deeper understanding of Netflix position within the industry. Then, in the third chapter, a financial analysis is conducted to assess Netflix financial performance and growth prospects. In the next chapter, after establishing some assumptions to project the value drivers, it was performed the valuation of the company through a Discounted Cash Flow (DCF) model. Additionally, a valuation based on market multiples was also presented to complement the DCF valuation. After that, in the investment risks section, a sensitivity analysis is conducted to evaluate the impact of key inputs on the DCF valuation and the possible scenarios of the intrinsic share price. Lastly, based on the valuation results and risk assessment is presented a final recommendation for investors, in the Investment Summary chapter.